The nucleosomal acidic patch relieves auto-inhibition by the ISWI remodeler SNF2h - Nathan Gamarra; Stephanie L Johnson; Michael J Trnka; Alma L Burlingame; Geeta J Narlikar (eLife, 2018)
ISWI family chromatin remodeling motors use sophisticated autoinhibition mechanisms to control nucleosome sliding. Yet how the different autoinhibitory domains are regulated is not well understood. Here we show that an acidic patch formed by histones H2A and H2B of the nucleosome relieves the autoinhibition imposed by the AutoN and the NegC regions of the human ISWI remodeler SNF2h. Further, by single molecule FRET we show that the acidic patch helps control the distance travelled per translocation event. We propose a model in which the acidic patch activates SNF2h by providing a landing pad for the NegC and AutoN auto-inhibitory domains. Interestingly, the INO80 complex is also strongly dependent on the acidic patch for nucleosome sliding, indicating that this substrate feature can regulate remodeling enzymes with substantially different mechanisms. We therefore hypothesize that regulating access to the acidic patch of the nucleosome plays a key role in coordinating the activities of different remodelers in the cell.